A comparative study of outcome of pyeloplasty in stented and non-stented children - Laddha, Ashok Kumar; Khare, Eeshansh; Lahoti, Brijesh Kumar (International Surgery Journal, 2019)
Background: It is a matter of debate whether to use a stent (double J) or not during pyeloplasty in patients of pelvic ureteric junction obstruction (PUJ obstruction). This study was conducted to assess which technique- stented or non-stented is better for paediatric patients with PUJ obstruction. Methods: 45 paediatric patients aged 0-12 years were included in this prospective comparative simple randomized sample study during the period of June 2015 to August 2017 in paediatric surgery division of department of surgery in M.Y. Hospital, Indore. All patients except one underwent open A-H dismembered pyeloplasty. The parameters used for comparison were renal parenchymal diameter, renal pelvis AP diameter, GFR (by DTPA scan) and rate of complications. Minimum follow up period was 3 months. Results: The M:F ratio was 2:1. Stented children had significant improvement in renal parenchymal diameter (i.e. increase) and GFR (of affected kidney) after pyeloplasty, whereas non-stented children too had improvement in renal parenchymal diameter and GFR (affected kidney) but was not significant. The percentage of postoperative complications were more in non-stented group as compared to stented group. Conclusions: In all paediatric cases with PUJO undergoing A-H pyeloplasty, both stenting and non-stenting have similar results and to place a double J stent should depend on choice of surgeon.